A shift in priority in diabetic foot care and research: 75% of foot ulcers are preventable. (January 2016) - Bus, Sicco A.; van Netten, Jaap J.
Abstract: Diabetic foot ulceration poses a heavy burden on the patient and the healthcare system, but prevention thereof receives little attention. For every euro spent on ulcer prevention, ten are spent on ulcer healing, and for every randomized controlled trial conducted on prevention, ten are conducted on healing. In this article, we argue that a shift in priorities is needed. For the prevention of a first foot ulcer, we need more insight into the effect of interventions and practices already applied globally in many settings. This requires systematic recording of interventions and outcomes, and well‐designed randomized controlled trials that include analysis of cost‐effectiveness. After healing of a foot ulcer, the risk of recurrence is high. For the prevention of a recurrent foot ulcer, home monitoring of foot temperature, pressure‐relieving therapeutic footwear, and certain surgical interventions prove to be effective. The median effect size found in a total of 23 studies on these interventions is large, over 60%, and further increases when patients are adherent to treatment. These interventions should be investigated for efficacy as a state‐of‐the‐art integrated foot care approach, where attempts are made to assure treatment adherence. Effect sizes of 75–80% may be expected. If such state‐of‐the‐art integrated foot care is implemented, the majority of problems with foot ulcer recurrence in diabetes can be resolved. It is therefore time to act and to set a new target in diabetic foot care. This target is to reduce foot ulcer incidence with at least 75%. Copyright © 2016 John Wiley & Sons, Ltd.